Membrane estrogen signaling in female reproduction and motivation - Johnson, Caroline S.; Micevych, Paul E; Mermelstein, Paul G. (Frontiers in Endocrinology, 2022)
Estrogen receptors were initially identified in the uterus, and later throughout the brain and body as intracellular, ligand-regulated transcription factors that affect genomic change upon ligand binding. However, rapid estrogen receptor signaling initiated outside of the nucleus was also known to occur via mechanisms that were less clear. Recent studies indicate that these traditional receptors, estrogen receptor  and estrogen receptor , can also be trafficked to act at the surface membrane. Signaling cascades from these membrane-bound estrogen receptors (mERs) not only rapidly effect cellular excitability, but can and do ultimately affect gene expression, as seen through the phosphorylation of CREB. A principal mechanism of neuronal mER action is through glutamate-independent transactivation of metabotropic glutamate receptors (mGluRs), which elicits multiple signaling outcomes. The interaction of mERs with mGluRs has been shown to be important in many diverse functions in females, including, but not limited to, reproduction and motivation. Here we review membrane-initiated estrogen receptor signaling in females, with a focus on the interactions between these mERs and mGluRs.